A civil aircraft passenger deplaning model considering patients with severe acute airborne disease. Issue 6 (2nd June 2022) - Xie, Chuan-Zhi; Tang, Tie-Qiao; Hu, Peng-Cheng; Huang, Hai-Jun
Abstract: The virus 2019-nCoV rapidly crossed the globe in the first quarter of 2020, and the global civil aviation industry contributed to the spread of the virus. The aircraft deplaning process is one of the critical stages of the spread of infectious diseases and merits careful research accordingly. However, little effort has been made to tailor the civil aircraft deplaning process to the existence of patients with severe acute airborne disease. In this study, we explore a mixed patient-health pedestrian deplaning flow from a Boeing 737-300's with a full economy-class layout as per the virus spread dynamics during the process. We develop feasible deplaning management strategies that can reduce the inflection risk to the healthy passengers during the deplaning process. We then quantitatively compare the deplaning process before and after adopting the proposed strategies. The numerical results show that the proposed strategies effectively reduce the risk of infection during the deplaning process but sacrifice deplaning efficiency. We assert that health outweighs efficiency, and find that the proposed strategy may thus have practical value and potentially be of use to administrators.